Rectal Perforation: A Rare Complication Following Uncomplicated Vaginal Delivery - Pun, Sunita; Poudel, Atit; Pant, Padam Raj (Journal of Nepal Health Research Council, 2021)
Rectal perforation during vaginal delivery is an uncommon event. It can cause complications including pelvic abscess and other life threatening illnesses, if not treated early. We here report a 24 years lady presented with a week long history of abdominal pain and fever associated with rectal discharge three weeks after uncomplicated vaginal delivery. Abdominal computed tomography findings suggestive of rectal perforation and revealed a huge pelvic abscess. A pigtail catheter was inserted into the pelvic abscess under transrectal ultrasound guidance and drained successfully. The patient recovered uneventfully and discharged 5 days after admission. Keywords: Pelvic abscess; rectal perforation; uncomplicated vaginal delivery